Future of Energy Demand by Microbial Fuel Cell: Review on Green Energy - Sahu, Omprakash; Kaur, Supreet; Dutt, Lovelesh (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 8 No 1 (2021): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
The colossal energy utilization in conjunction with the incrementing growth of population, made the need to develop energy assets. Energy sources accessible have been categorized into fossil fuels, nuclear and renewable energy sources based on their mode of origin and reliability. Microbial Fuel Cell is progressive in the future of environment protection. The technology will be nearer to realistic applications with the introduction of profoundly efficient electrode materials and catalysts to diminish production costs making it more sustainable. The primary components of fuel cells are electrodes i.e. anode and cathode. The anode is an electrode that induces oxidation and loss of electrons. The cathode is where there is reduction and the production of electrons. Anode surface fuel oxidation produces electrons and oxidized by-products. The electrons later pass through an external circuit to the cathode. Microbes absorb nutrients from their surrounding environment within the MFC and release in the form of bioelectricity.